2021
DOI: 10.16882/hortis.1012446
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of the COVID-19 Pandemic on the Prices of Basic Food Sold in Traditional Markets: The Case of Jakarta Province, Indonesia

Abstract: The purpose of this study was to analyze the development and fluctuation of basic food prices in traditional markets in Jakarta before and during the coronavirus disease (COVID-19) pandemic. The study used performance reports from the Indonesian Central Statistical Institute (BPS), National Center for Food Price Information (PHPI), various government agencies, the latest news from reliable online media, and similar studies. The scope of the research focused on the development of basic food prices in traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This means that people who eat more whole food have better diet quality. The economically impacted people's food expenses, which means that cheaper food such as processed food is most likely to be available and readyto-eat (Chianardi & Permatasari, 2020;Paganini et al, 2020;Pingali & Abraham, 2022;Zahraturrahmi et al, 2021). People with degenerative diseases, such as diabetes and coronary heart disease, are more prone to COVID-19 than those without degenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that people who eat more whole food have better diet quality. The economically impacted people's food expenses, which means that cheaper food such as processed food is most likely to be available and readyto-eat (Chianardi & Permatasari, 2020;Paganini et al, 2020;Pingali & Abraham, 2022;Zahraturrahmi et al, 2021). People with degenerative diseases, such as diabetes and coronary heart disease, are more prone to COVID-19 than those without degenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The economy has been impacted by the pandemic and hence affected the prices of food and non-food, including cigarettes (Galiani, 2022;Sparrow et al, 2020;Susilawati et al, 2020;Zahraturrahmi et al, 2021). This study investigates people's spending on food and nonfood during the pandemic, and how their daily expenses impact diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies even found a substantial increase in the price of food commodities that, to a certain degree, leads to food hoarding (Singh et al, 2020, Borgards et al, 2021, and Cariappa et al, 2021. Meanwhile, studies on Indonesia are scarce and limited to a few strategic food commodities (Nendissa et al, 2020, Medah 2020, Rahmanta & Maryunianta 2020, Wulandari 2020, Pricilia, 2021, and Zahraturrahmi et al, 2021. They used descriptive analyses which may not capable of providing strong inferences about causal relationships.…”
Section: Source: Bpsmentioning
confidence: 99%